Startled Stomach: Contemporary Indigeneity and Sensorial “Culture Shock” in Aljenljeng Tjaluvie’s Paiwan Pop Music - Yu, Yi-Jen (Performance Matters, 2024)
In 2016, Aljenljeng ended a thirteen-year hiatus and returned to the pop music scene in Taiwan with her first solo album, all in the Paiwan language, Vavayan. Formerly a Mandopop singer, Aljenljeng used to be known by the Chinese stage name Abao and sang only in Mandarin Chinese. Her choice to compose and sing the whole album in Paiwan signals a critical re-evaluation of Mandopop culture and its lyrical paradigm, which normalized Mandarin monolingualism as both the index of musical modernity in Taiwan and the lingua franca of Mandopop’s internationalization during the 1990s and early 2000s. Aljenljeng’s Paiwan turn was an effort to disrupt both Mandopop’s consumption of Indigenous music in Taiwan and the settler structure of feeling. Aljenljeng’s audiovisual expressions, sensorial experiences, and depictions of contact between Indigenous and non-Indigenous cultures in Taiwan generate meaningful Indigenous-initiated transcultural conversations. Aljenljeng’s video for “Minetjus” (which translates as “startled” or “shocked”) counters settler (over)consumption by placing settler, rather than Indigenous, individuals in the position of being observed, absorbed, transformed, and compelled to adapt. Amid the rhythmic naming of an array of Paiwan dishes in the song and video, the singer playfully cautions, “Don’t eat too much, otherwise your stomach will be startled.” Here, the Paiwan idiom for stomachache, “to have one’s stomach startled/shocked,” signifies both an openness to intercultural exposure and a rejection of the settler desire to digest and consume. Extending from the music tradition of the Paiwan, one of the sixteen Indigenous nations on the island, Aljenljeng’s work affirms intercultural curiosity on the premise of Indigenous sensory and emotional sovereignty, further fostering the possibility of interethnic dialogue in multicultural contemporary Taiwan.